Synthesis and characterization of peanut shell-derived ferromagnetic activated carbon: application in the Fenton process for the degradation of methyl orange - Ndongmo, Josiane Nguimatsia; Mabou, Jules Leuna; Tchuifon Tchuifon, Donald Raoul; Makota, Suzanne; Fotsop, Cyrille Ghislain; Conde, Miriame; Tchieta, Pierre Gerard (Frontiers in Environmental Chemistry, 2024)
The objective of the current work was to synthesise and characterize a ferromagnetic activated carbon from peanut shells and apply it for the degradation of methyl orange following the heterogeneous Fenton process. Peanut shells(PS) were activated with phosphoric acid and potassium hydroxide at 1:1; 1:2 and 1:3 solid/liquid activation ratios and different concentrations (0.5, 1 and 1.5 M) and pyrolized at 500°C. Based on the iodine indices, KOH-activated carbon adsorbents exhibited higher porosity than the H3PO4 activated adsorbents. KOH-activated carbon at 1:3 activation ratio (iodine value 591 mg/g) was selected for magnetization using iron (II) ions and catalytic mineralization of MO dye. The ferromagnetic activated carbon (AC-PS@FeII) was characterized using Fourier Transform Infrared Spectroscopy (FTIR), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive analysis of X-rays (EDX) and nitrogenadsorption BET measurements. AC-PS@FeII contained ferromagnetite with cubic spinel structure and a specific area of 181.96 m 2 •g -1 . The AC-PS@FeII posted 99.22% MO degradation efficiency at pH 2, 4g/L of catalyst dosage, and 50 min contact time. Results of recyclability tests, using distilled water, revealed a slight decrease in degradation capacity after four runs indicating that the developed catalyst was appreciably stable. The hetero-Fenton catalyst from peanut shells could be an ideal catalyst for treating wastewater contaminated with dyes as a path towards circular economy.